Polyclonal selection of immune checkpoint mutations in thyroid autoimmunity - Pantelis A. Nicola; Andrew R. J. Lawson; Alexandra Tidd; Juliette Imbert; Yoshihiro Ishida; Luke A. Wylie; Paul A. Scott; Kenny Roberts; Luke M. R. Harvey; Stefanie V. Lensing; Wei Cheng; Federico Abascal; et al. (Nature, 2026)
Abstract Our immune system contains multiple checkpoints to prevent the activation of self-reactive lymphocytes. How some lymphocytes escape these constraints to cause autoimmune disease remains poorly understood. A long-standing hypothesis posits that somatic mutations in immune regulatory genes may enable self-reactive lymphocytes to bypass tolerance checkpoints 1–3 , but testing this has been challenging owing to technical limitations. Here we used whole-exome and targeted NanoSeq 4,5 , an accurate single-molecule DNA sequencing protocol, to comprehensively search for driver mutations in autoimmune thyroid disease. This showed many B cell clones convergently acquiring loss-of-function mutations in the key immune checkpoint genes TNFRSF14 (also known as HVEM ) and CD274 (which encodes PD-L1), as well as less frequent mutations in other immune genes. In highly inflamed biopsies, we detected tens to hundreds of independent immune checkpoint mutant clones. Laser microdissection, methylation sequencing, spatial transcriptomics, immunostaining, single-nucleus DNA sequencing and antibody synthesis localized these mutations to B cells, confirmed some to be self-reactive and identified clones carrying multiple hits. We found widespread TNFRSF14 biallelic loss, and clones with as many as 4–6 driver mutations. While each clone accounts for a small fraction of cells (typically less than 1%), the myriad mutant clones in each donor amounted to a substantial fraction of B cells harbouring driver mutations. Our results support the hypothesis that somatic mutations in autoimmune lymphocytes may allow them to escape tolerance constraints through a polyclonal cascade of somatic evolution, providing insights into the molecular basis of autoimmune disease.